APLICATION OF ETHYLENE ABSORBEN PACKAGING ON GUAVA (Psidium guajava L.) STORAGE - Novita, Dwi Dian (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
Ethylene production of guava fruit (Psidiumguajava L.) increased in ripening phase. Tomaintain the quality of fruit so the ethylene should be reduced fromstorage roomto inhibited respiration rate. The aims of this research were: (1) to find out the effect of KMnO4 against guava shelflife based on weight lose, hardness, soluble solid content, and vitaminC as parameters, and (2) to known the best treatment. The researchwas use experimental desainwith 5 treatmentswereP0=without KMnO4,P1=0,6gKMnO4+absorber, P2=1,2g KMnO4+absorber,P3=1,8g KMnO4+absorber, dan P4=2,4g KMnO4+absorber and 4 repeatation. Datawas analized by Annova and Duncan Test at Ã¡=5%. The result showed that shelflife of guava treated by KMnO4was 8 dayswhilewithout KMnO4was 6 days. Based on Annova at Ã¡=5%, KMnO4 treatment was significant on weight lose and hardness parameters butwas not significant on soluble solid content and vitamin C parameters. The best treatment in this researchwas P4 (2,4g KMnO4+absorber). Keywords: ethylene,KMnO4, guava, shelflife